2022
DOI: 10.3390/f13020174
|View full text |Cite
|
Sign up to set email alerts
|

Upward Treeline Shifts in Two Regions of Subarctic Russia Are Governed by Summer Thermal and Winter Snow Conditions

Abstract: Climate warming impacts on alpine treeline dynamics. However, we still lack robust assessments of the long-term impacts of climate on tree recruitment at the treeline, particularly in remote areas such as the subarctic regions of Russia subjected to different climate influences. We expected that the treelines in two regions may have different features and dynamics patterns. We analyzed climate variables and assessed treeline dynamics by quantifying recruitment using the tree rings of ca. 7000 trees of four spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
1
5
0
1
Order By: Relevance
“…The results of our research have shown that the survival and, consequently, further growth and development of Pinus sibirica, are due to climate warming. This conclusion is in good agreement with the results of research (including other tree species) on the Polar Urals [16,48], the Khibiny Massif (Kola Peninsula) [49], the western Putorana Plateau [48,49] in the Southern Rockies (region of northern New Mexico and southern Colorado) [50], in the Himalayas [51], and in the southern European range (the Pyrenees) [52]. The obtained results complement the meta-analysis of annual tree line shift rates at 143 sites from 38 published studies [53] and clarify the impact temperature and precipitation have on Pinus sibirica regeneration.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of our research have shown that the survival and, consequently, further growth and development of Pinus sibirica, are due to climate warming. This conclusion is in good agreement with the results of research (including other tree species) on the Polar Urals [16,48], the Khibiny Massif (Kola Peninsula) [49], the western Putorana Plateau [48,49] in the Southern Rockies (region of northern New Mexico and southern Colorado) [50], in the Himalayas [51], and in the southern European range (the Pyrenees) [52]. The obtained results complement the meta-analysis of annual tree line shift rates at 143 sites from 38 published studies [53] and clarify the impact temperature and precipitation have on Pinus sibirica regeneration.…”
Section: Discussionsupporting
confidence: 91%
“…This is a certain combination of thermal and hydrological factors that drives treeline shift rates across the Northern Hemisphere [53]. The combination may include temperatures in early summer and precipitation in early winter [48,49], temperature-moisture correlations throughout the year [50], winter precipitation only (high snow depth) [14], and winter temperatures [54]. Our research shows the greatest correlation between Pinus sibirica regeneration and the maximum temperatures in May and June of the previous year.…”
Section: Discussionmentioning
confidence: 71%
“…Consequently, the snow cover depth at the beginning of the cold period also increased significantly by +3.3 cm per decade -1 and by +5.2 cm per decade -1 , respectively. For the Khibiny Mountains, we observed a high positive correlation between tree recruitment (birch and pine) and precipitation in July and during the beginning of the cold period (November-December), as well as with the snow depth at the beginning of the cold period [44]. Correlation analysis also showed that on the Putorana Plateau there were positive relations between the number of larches recruiting between 1910 and 2010 and the temperature indicators for the warm period, total precipitation at the beginning of the cold period (October-December), and snow depth at the end of December [44].…”
Section: Climate and Stands Changesmentioning
confidence: 76%
“…Для Хибин факт повышенного биологического разнообразия был установлен почти 100 лет назад сотрудниками первой научной горной станции «Тиетта» [Фридолин, 1934] и неоднократно подтвержден последующими исследованиями [Зенкова, 2020]. При-мером ответной реакции горных экосистем на воздействие глобальных и региональных факторов является высотное продвижение границы леса на фоне повышения среднегодовых температур воздуха, фиксируемое в последние десятилетия от Алтае-Саянской горной провинции на юге Сибири до гор Европейского Северо-Востока России, Скандинавских гор и Хибин [Крючков, 1958а, б;Kullman, 2007;Шиятов, 2009;Моисеев и др., 2010, 2016Петров и др., 2021;Тютькова и др., 2021;Каверин, 2022;Grigoriev et al, 2022].…”
Section: Fig 3 a Fragment Of An Attribute Table Of The Information Sy...unclassified